Pengaruh Berbagi Pengetahuan terhadap Kinerja Karyawan melalui Kerja Tim - Noer Chalifa; Dwiarko Nugrohoseno (Universitas Negeri Surabaya, 2018)
PT. Boma Bisma Indra (Persero) Surabaya is a companyengaged in the field of energy conversion industry, industrial machinery, and infrastructure industries. All business activities are based on the formation of work teams are formed according to the needs of the company. The purpose of this study was to analyze the influence of knowledge sharing, kerja tim, employee performance. Teamwork as well as the mediating role of knowledge sharing on the performance. Samples from this study were all employees totaling 84 people. The data analysis technique used is Structural Equation Model of Partial Least Square with the help of software SmartPLS 2.0 M3. The results of the study explains that knowledge sharing significant effect on the performance of employees, knowledge sharing significant effect on teamwork, teamwork significant effect on employee performance. kerja tim does not mediate the effect of knowledge sharing on the performance of employee